Gas Leakage Detection and Automatic Booking using GSM - Arun Prakash.A, Jeyaramya R, Miruthula S (International Journal of Advanced Science and Technology, 2020)
Guaranteed protection and safety of home or an industry is nowadays becoming a menacing factor. One of the biggest threats is gas leakage from cylinders. This can cause mammoth wreckage ensuing in seconds. Such gas leakage can occur in cases where the rubber tubing or the regulator fitting is shoddy. The idea presented in this paper is to continuously monitor the weight of the gas being consumed and also to prevent any misadventure that may occur due to gas leakage. The proposed design uses Atmega8 microcontroller, which monitors the weight of the LPG cylinder continuously by measuring the signal generated by the Load cell. If the cylinder is close to being fully empty, then it will notify by sending a message to the user and then to the web server and hence transfer message to an LPG agency for ordering another cylinder. The design also includes the alerting mechanism which alerts the user when there is a leakage of gas. This is done by using a gas leakage sensor and here, MQ-2 sensor is used. In case of gas leakage, it will be detected and the user will be alerted by a buzzer and simultaneously a text message will be sent to the corresponding user. Index terms: Atmega8 microcontroller, Automatic gas booking, Gas leakage detection, GSM module, Load cell, MQ-2 gas sensor.